Ruralities, territorial focus and public policies for rural development in Brazil: an abandoned priority? Ruralidades, enfoque territorial e políticas públicas diferenciadas para o desenvolvimento rural brasileiro: uma agenda perdida? - Pereira Leite, Sergio (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2020)
This paper invites a reflection on “styles” or “models” of development that have characterized social, economic and politico-institutional transformations in rural areas. It does so by evaluating territorial development, differentiated public policies, and the emergence of new ruralities in the agricultural context in Brazil, based on the experience over the last few decades. By drawing on international literature, this work assesses the meaning of the use of new ruralities to characterise farming environments, and its impact over important indicators and governmental policies. With a focus on Brazil, the article traces recent processes that help to sketch out possible “snapshots” of the national agricultural landscape, as evidenced in work based on land grabbing and financialization of land, and on the constitution of rural territories. These processes are supported by important governmental policies, such as rural credit and territorial development programs. The recent crisis of agricultural policies in Brazil brings new challenges in terms of understanding this broader context, and raises new questions, which will be addressed in the concluding remarks. Keywords: rural development; territorial development; agricultural policies; ruralities.LEITE, Sergio Pereira. Ruralidades, enfoque territorial e políticas públicas diferenciadas para o desenvolvimento rural brasileiro: uma agenda perdida? Estudos Sociedade e Agricultura, v. 28, n. 1, p. 227-254, fev. 2020.Submitted on November 19, 2019.Accepted on January 6, 2020.